Relevance of testicular histopathology on prediction of sperm retrieval rates in case of non-obstructive and obstructive azoospermia. Issue 2 (May 2018) - Cito, Gianmartin; Coccia, Maria E; Dabizzi, Sara; Morselli, Simone; Della Camera, Pier A; Cocci, Andrea; Criscuoli, Luciana; Picone, Rita; De Carlo, Candida; Nesi, Gabriella; Micelli, Elisabetta; Serni, Sergio; et al.
Introduction: The aim of our research was to establish the relevance of testicular histopathology on sperm retrieval after testicular sperm extraction in patients with non-obstructive azoospermia and in patients with obstructive azoospermia, who already underwent a previous failure testicular fine needle aspiration. Methods: We evaluated a total of 82 azoospermic men, underwent testicular sperm extraction, referring to the Assisted Reproductive Technology Centre of the University of Florence, Italy between January 2008 and March 2017. A general and genital physical examination, scrotal and trans-rectal ultrasound, semen analysis, hormone measurements, including follicle-stimulating hormone, luteinizing hormone and total testosterone, were collected. Results: Successful sperm retrieval was obtained in 36 men of total (43.9%). Successful sperm retrieval was 29.5% in non-obstructive azoospermia patients, while men with obstructive azoospermia, who, underwent a previous failure testicular fine needle aspiration, had sperm retrieval in 86% of cases. Mean luteinizing hormone was 6.55 IU/L, total testosterone 4.70 ng/mL, right testicular volume 13.7 mL and left testicular volume 13.6 mL. Mean Follicle-stimulating hormone was 13.45 IU/L in patients with negative sperm retrieval and 8.18 IU/L in men with successful sperm retrieval. According to histology, 20.7% had normal spermatogenesis, 35.3% hypospermatogenesis, 35.3% maturation arrest and 8.5% Sertoli cell-only syndrome. Successful sperm retrieval was 88.2% in patients with normal spermatogenesis, 24.1% in the maturation arrest group and 48.27% in patients with hypospermatogenesis, while negative sperm retrieval was reported in Sertoli cell-only syndrome patients. Seven cases with maturation arrest showed a successful sperm retrieval. Conclusion: Testicular histopathology after testicular sperm extraction offers important information on prediction of sperm retrieval and can guide the surgeon in choosing the more suitable therapeutic practice.